Penyuluhan Perilaku Hidup Bersih dan Sehat pada Anak dengan HIV/AIDS di Yayasan Lentera Kota Surakarta - Syarifah; Restu Febriyanti, Rachmanita; Almas Aqilah (Darma Abdi Karya, 2024)
This community service activity targets children with HIV/AIDS (ADHA). Children with HIV-AIDS (ADHA) present particular challenges related to issues such as adherence to a regimen of therapy that must be taken constantly. Issues such as stigma, discrimination, depression, drug abuse, and the prevention of further transmission can also be intimidating at this age. The basic thing that needs to be provided is socialization and counseling regarding Clean and Healthy Living Behavior (PHBS) which will be their behavior in the future. How they will behave healthily will affect their health. The research objective is to determine the effectiveness of providing counseling on clean and healthy living behaviors to children with HIV/AIDS at the Lentera Foundation of Surakarta City. This type of service activity is preceded by a pretest which aims to measure children's knowledge before being given counseling. Then counseling was given aboutMethod: This type of service activity is preceded by a pretest which aims to measure children's knowledge before being given counseling. Then counseling was given about related materials, after which a post test was carried out with the material that had been given which aimed to measure children's knowledge after being given counseling. The service conducted a pretest with the aim of seeing the level of understanding of counseling participants before counseling, the results of the pre test and post test were very different. The result of the post test is very good, namely 94.10, indicating that the material that has been delivered by the extension worker has been understood correctly, so that the results of the post test with the same questions are very good.